Construction and optimization of the cold storage process based on phase change materials used for liquid air energy storage system. (September 2021) - Chen, Jiaxiang; An, Baolin; Yang, Luwei; Wang, Junjie; Hu, Jianying
Highlights: A novel method was proposed to store cold for liquid air energy storage system. The effect of parameters on cold storage stage number was originally analyzed. A method to optimize the cold storage unit was studied by using liquid fluids (LF). An innovative cold storage unit with LF and phase change materials was obtained. Abstract: This paper presents a liquid air energy storage (LAES) system using phase change materials (PCMs) as cold storage mediums. The influence of the energy storage pressure, the energy release pressure, and the minimum heat transfer temperature difference on the cold storage stage number has been originally studied. The results revealed that the system features the largest number of cold storage stages under the optimum energy storage pressure and energy release pressure, and reducing the energy storage pressure can significantly level the cold storage stages. While decreasing the minimum heat transfer temperature difference can improve the energy storage efficiency, it will increase the cold storage stages most of the time. The sensible heat of the glycol solution is introduced at the hot end of the cold storage unit to further cut down the cold storage stage number. At last, 12 kinds of PCMs, along with the glycol solution are selected to construct a complete cold storage unit.